Mixed Responses to Systemic Therapy Revealed Potential Genetic Heterogeneity and Poor Survival in Patients with Non‐Small Cell Lung Cancer. (17th January 2017) - Dong, Zhong‐Yi; Zhai, Hao‐Ran; Hou, Qing‐Yi; Su, Jian; Liu, Si‐Yang; Yan, Hong‐Hong; Li, Yang‐Si; Chen, Zhi‐Yong; Zhong, Wen‐Zhao; Wu, Yi‐Long
Abstract : Background: A subset of patients with non‐small cell lung cancer (NSCLC) fosters mixed responses (MRs) to epidermal growth factor receptor (EGFR)‐tyrosine kinase inhibitors (TKIs) or chemotherapy. However, little is known about the clinical and molecular features or the prognostic significance and potential mechanisms. Methods: The records of 246 consecutive patients with NSCLC receiving single‐line chemotherapy or TKI treatment and who were assessed by baseline and interim positron emission tomography/computed tomography scans were collected retrospectively. The clinicopathological correlations of the MR were analyzed, and a multivariate analysis was performed to explore the prognostic significance of MR. Results: The overall incidence of MR to systemic therapy was 21.5% (53/246) and predominated in patients with stage IIIB–IV, EGFR mutations and those who received TKI therapy ( p < .05). Subgroup analyses based on MR classification (efficacious versus inefficacious) showed significant differences in subsequent treatment between the two groups ( p < .001) and preferable progression‐free survival (PFS) and overall survival (OS) in the efficacious MR group. Multivariate analyses demonstrated that the presence of MR was an independent unfavorable prognostic factor for PFS (hazard ratio [HR], 1.474; 95% confidence interval [CI], 1.018–2.134; p = .040) and OS (HR, 1.849; 95% CI, 1.190–2.871; p = .006) in patients with NSCLC. Induced by former systemic therapy, there were more T790M (18%), concomitant EGFR mutations (15%), and changes to EGFR wild type (19%) in the MR group among patients with EGFR mutations, which indicated higher incidence of genetic heterogeneity. Conclusion: MR was not a rare event in patients with NSCLC and tended to occur in those with advanced lung adenocarcinoma treated with a TKI. MR may result from genetic heterogeneity and is an unfavorable prognostic factor for survival. Further studies are imperative to explore subsequent treatment strategies. Abstract : The occurrence and prognostic significance of mixed responses to systemic therapies among patients with non‐small cell lung cancer were evaluated by positron emission tomography/computed tomography scans (PET/CT) to provide comprehensive measurements of each lesion. Clinical biomarkers were explored to identify potential molecular mechanisms resulting in mixed response. The results of this study may help us to understand the clinical and molecular features of mixed response and provide a foundation to explore subsequent therapeutic strategies.